Isolation of Messenger RNA Coding for Mouse Heavy-Chain Immunoglobulin - Stevens, R. H. (1973)
A method for purification of the mRNA coding for heavy-chain protein of a mouse G(2a) myeloma (5563) is reported. Complete myeloma protein (H(2)L(2)) specifically binds to the heavy-chain mRNA, and the resultant RNA-protein complex is precipitated with antiserum against 5563 myeloma protein. Cytoplasmic RNA isolated by this method showed two bands of 6.0 × 10(5) and 3.1 × 10(5) molecular weight when analyzed by acrylamide gel electrophoresis. The RNA in the bands contained 1.5% and 8% A-rich regions, respectively. The RNA in each of the bands contained sequences for heavy-chain protein when translated in Xenopus laevis oocytes.